Experimental and Theoretical Examination of Low-Current Overcharge at Lithiated-Graphite Porous Electrodes. Issue 8 (7th May 2020) - Verbrugge, Mark W.; Xiao, Xingcheng; Baker, Daniel R.
Abstract : We determine if a recently developed model for describing the thermodynamics of lithiated graphite in equilibrium with plated Li (lithium) is consistent with well-controlled, low-current-density experiments that lead to Li plating on lithiated graphite. We show through numerical differentiation of the experimental data how to identify when Li plating is taking place. Plating (overcharge) occurs well before the electrode potential falls to 0 V vs Li, which is consistent with underpotential deposition of Li on graphite. This observation (i) cannot be reproduced by today's porous electrode models that do not incorporate the underpotential deposition of Li on the graphite surface, and (ii) is consistent with the Li activity model recently developed.